Norepinephrine Infusion and the Central Venous Waveform in a Porcine Model of Endotoxemic Hypotension with Resuscitation: A Large Animal Study - Zachary R. Bergman; Roy K. Kiberenge; Richard W. Bianco; Gregory J. Beilman; Colleen M. Brophy; Kyle M. Hocking; Bret D. Alvis; Eric S. Wise (Journal of Investigative Surgery)
Background Venous waveform analysis is an emerging technique to estimate intravascular fluid status by fast Fourier transform deconvolution. Fluid status has been shown proportional to f0, the amplitude of the fundamental frequency of the waveform’s cardiac wave upon deconvolution. Using a porcine model of distributive shock and fluid resuscitation, we sought to determine the influence of norepinephrine on f0 of the central venous waveform.Methods Eight pigs were anesthetized, catheterized and treated with norepinephrine after precipitation of endotoxemic hypotension, and subsequent fluid resuscitation to mimic sepsis physiology. Hemodynamic parameters and central venous waveforms were continually transduced throughout the protocol for post-hoc analysis. Central venous waveform f0 before, during and after norepinephrine administration were determined using Fourier analysis.Results Heart rate increased, while central venous pressure, pulmonary capillary wedge pressure and stroke volume decreased throughout norepinephrine administration (p < 0.05). Mean f0 at pre-norepinephrine, and doses 0.05, 0.10, 0.15, 0.20 and 0.25 mcg/kg/min, were 2.5, 1.4, 1.7, 1.7, 1.6 and 1.4 mmHg2, respectively (repeated measures ANOVA; p < 0.001). On post-hoc comparison to pre-norepinephrine, f0 at 0.05 mcg/kg/min was decreased (p = 0.04).Conclusions As the performance of f0 was previously characterized during fluid administration, these data offer novel insight into the performance of f0 during vasopressor delivery. Central venous waveform f0 is a decreased with norepinephrine, in concordance with pulmonary capillary wedge pressure. This allows contextualization of the novel, venous-derived signal f0 during vasopressor administration, a finding that must be understood prior to clinical translation.